2001
DOI: 10.1146/annurev.physiol.63.1.647
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of Mammalian Circadian Rhythms

Abstract: In mammals, a master circadian "clock" resides in the suprachiasmatic nuclei (SCN) of the anterior hypothalamus. The SCN clock is composed of multiple, single-cell circadian oscillators, which, when synchronized, generate coordinated circadian outputs that regulate overt rhythms. Eight clock genes have been cloned that are involved in interacting transcriptional-/translational-feedback loops that compose the molecular clockwork. The daily light-dark cycle ultimately impinges on the control of two clock genes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
1,047
0
25

Year Published

2002
2002
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,317 publications
(1,104 citation statements)
references
References 145 publications
32
1,047
0
25
Order By: Relevance
“…Per proteins typically regulate the timing of gene expression by repressing gene transcription [44]. Consistent with this, we found that exorh transcripts were up-regulated during the day in embryos injected with a per3 MO ( Figure 3B, C).…”
Section: Per3 Negatively Regulates Exorh Transcription During the Daysupporting
confidence: 82%
See 1 more Smart Citation
“…Per proteins typically regulate the timing of gene expression by repressing gene transcription [44]. Consistent with this, we found that exorh transcripts were up-regulated during the day in embryos injected with a per3 MO ( Figure 3B, C).…”
Section: Per3 Negatively Regulates Exorh Transcription During the Daysupporting
confidence: 82%
“…While the functions of vertebrate Per1 and Per2 proteins are well established, the function of Per3 has been difficult to define. In mice, Per1 and Per2 have central roles in the feedback loops of the circadian clock and in resetting the clock in response to environmental light cues [44]. In contrast, per3 knock out mice have only a slight decrease in the period of their circadian clock [51].…”
Section: The Pattern Of Exorh Transcription Is Controlled By a Combinmentioning
confidence: 99%
“…The primary molecular clock is located in the suprachiasmatic nucleus (SCN) in the hypothalamus, and consists of a transcriptional feedback loop which cycles over the course of approximately twenty-four hours in the absence of environmental input (Reppert and Weaver, 2001; Ko and Takahashi, 2006). The major transcriptional activator consists of a dimer between the Circadian Locomotor Output Cycles Kaput Protein (CLOCK) and Brain and Muscle ARNT-like Protein 1 (BMAL1, also known as ARNTL or MOP3).…”
Section: The Molecular Clockmentioning
confidence: 99%
“…Daily rhythms are prominent in everything from sleep/wake cycles, body temperature, hormone levels, and even cognition, attention and mood (Bunney and Bunney, 2000;Reppert and Weaver, 2001). Disruptions in biological rhythms are known to be strongly associated with mood disorders.…”
Section: Introductionmentioning
confidence: 99%
“…In the mouse, for example, clock and bmall form a promoter complex driving the expression of clock and clock controlled genes. PERI-3 proteins, phosphorylated via casein kinase IE (CKIE), form heterodimers with CRY1 and CRY2 proteins in the cytoplasm, allowing nuclear trans location^ and negative feedback on gene transcription (Dunlap, 1999;Okamura et al, 2002;Preitner etal., 2002;Reppert & Weaver, 2001). This mechanism results in a self-sustained oscillation of clock and clock controlled gene e:wpression.…”
Section: Scn Physiology and Putative Molecular Geneticsmentioning
confidence: 99%